2015
DOI: 10.1111/acer.12891
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in Alcohol Intake Predicts Reinforcement, Motivation, and Compulsive Alcohol Use in Rats

Abstract: These profound individual differences in alcohol intake, reinforcement, motivation, and AUD-like behavior provide a promising tool to unravel the neurobehavioral underpinnings of individual vulnerability for AUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 49 publications
14
62
0
Order By: Relevance
“…The rapid development of aversion-resistant alcohol drinking in C57BL/6 mice is in strong contrast to rats, where several months of intermittent alcohol intake are required for Wistar rats to develop quinine-resistant drinking patterns (Hopf and Lesscher, 2014, Hopf et al, 2010, Loi et al, 2010, Seif et al, 2013, Seif et al, 2015 and Spoelder et al, 2015). Although there are many species differences that might explain these dissimilarities, one clear finding is that C57BL/6 mice drink high levels of alcohol from the onset, with binge-like levels of alcohol intake even during a first, 4-h drinking session (Mulligan et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…The rapid development of aversion-resistant alcohol drinking in C57BL/6 mice is in strong contrast to rats, where several months of intermittent alcohol intake are required for Wistar rats to develop quinine-resistant drinking patterns (Hopf and Lesscher, 2014, Hopf et al, 2010, Loi et al, 2010, Seif et al, 2013, Seif et al, 2015 and Spoelder et al, 2015). Although there are many species differences that might explain these dissimilarities, one clear finding is that C57BL/6 mice drink high levels of alcohol from the onset, with binge-like levels of alcohol intake even during a first, 4-h drinking session (Mulligan et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Understanding these different types of motivation for alcohol may reveal subpopulations of alcohol use disorders, each with different neural substrates and different potential treatments. It is also important to note that some studies have demonstrated that, after approximately 2 months of homecage ethanol access, high-drinking animals show stronger operant ethanol seeking than do low-drinking animals (Spoelder et al, 2015). Therefore, it is possible that we may have observed a stronger relationship between homecage alcohol intake and self-administration in HR and LR rats had the homecage access period extended beyond two weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported individual differences in alcohol preference in outbred rats (e.g., Momeni and Roman, 2014; Momeni et al, 2014; Pelloux et al, 2015; Sharko et al, 2013; Spoelder et al, 2015), though it is more common for studies to consider effects averaged across entire cohorts. The current results, combined with previous work from our lab (Lopez et al, 2016; Moorman and Aston-Jones, 2009), strongly indicate that these individual differences in ethanol motivation result, at least in part, from differential activation of the ORX system.…”
Section: Discussionmentioning
confidence: 99%
“…Since shock-resistant intake is considered to have face and predictive validity for compulsive intake in humans, e.g. for cocaine (Everitt and Robbins, 2005; Hopf and Lesscher, 2014; Lesscher and Vanderschuren, 2012), the observation of a similar circuit for shock- and quinine-resistant alcohol drinking (Seif et al, 2013) validates the use of alcohol-quinine drinking to model compulsive-like drives for alcohol (Hopf et al, 2010; Hopf and Lesscher, 2014; Lesscher et al, 2010; Loi et al, 2010; Marchant et al, 2013; Spanagel and Holter, 1999; Spoelder et al, 2015; Vengeliene et al, 2009). For the present studies, we utilized a recently developed compulsive-like drinking model in mice, modified from Lesscher et al (2010) where aversion-resistant alcohol drinking is apparent after only a single protracted session of alcohol-only consumption, and with binge-like blood alcohol levels (Lei et al, in press).…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, to effectively reduce the impact of AUDs, it is critical to understand the mechanisms that drive this consequence-resistant, compulsive-like alcohol consumption. In this regard, voluntary drinking paradigms, where animals will drink despite pairing the alcohol with an aversive consequence (such as bitter-tasting quinine or foot-shock), have been utilized to model some compulsive-like aspects of AUDS in humans (Hopf et al, 2010; Hopf and Lesscher, 2014; Lesscher et al, 2010; Loi et al, 2010; Marchant et al, 2013; Spanagel and Holter, 1999; Spoelder et al, 2015; Vengeliene et al, 2009). In addition, we previously demonstrated that a similar corticoaccumbens circuit promotes both shock-resistant and quinine-resistant alcohol drinking (Seif et al, 2013).…”
Section: Introductionmentioning
confidence: 99%